Penyuluhan Penerapan Protokol Kesehatan bagi Karyawan di Kelurahan Pluit, Kecamatan Penjaringan, Jakarta Utara - Chondro, Fransisca; Juni Chudri; Lily Marliany Surjadi; Astri Handayani (CV. Multi Kreasi Media, 2022)
Coronavirus infection disease (COVID-19) is a disease caused by the Sars-Cov2 virus and the first case was found in the city of Wuhan, China and then rapidly transmitted to other countries all over the world. On March 2020, World Health Organization (WHO) declared this disease as a pandemic. Until now, there are 232.468.228 cases and 4.759.804 death worldwide. This virus had mutated and there are some variants of virus that found during this pandemic with variety of symptoms. Regardless the high morbidity rate of this virus, this pandemic also had effect on the economy sector. Hence, many countries started to give permission to companies to start their activity normally. The incremental activities of the workers with higher mobility rate can cause the higher transmission rate of this disease. Therefor, it is very important to educate the people, especially the workers, about the implementation of health protocol in order to prevent transmission of this disease between workers in the workplace or between worker and their family at home. health protocol, transmission, worker, mask